Water Reuse: From Ancient to Modern Times and the Future - Angelakis, Andreas N.; Asano, Takashi; Bahri, Akissa; Jimenez, Blanca E.; Tchobanoglous, George (Frontiers in Environmental Science, 2018)
From the beginning of the Bronze Age (ca. 3200–1100 BC), domestic wastewater (sewage) has been used for irrigation and aquaculture by a number of civilizations including those that developed in China and the Orient, Egypt, the Indus Valley, Mesopotamia, and Crete. In historic times (ca. 1000 BC−330 AD), wastewater was disposed of or used for irrigation and fertilization purposes by the Greek and later Roman civilizations, especially in areas surrounding important cities (e.g., Athens and Rome). In more recent times, the practice of land application of wastewater for disposal and agricultural use was utilized first in European cities and later in USA. Today, water reclamation and reuse projects are being planned and implemented throughout the world. Recycled water is now used for almost any purpose including potable use. This paper provides a brief overview of the evolution of water reuse over the last 5,000 years, along with current practice and recommendations for the future. Understanding the practices and solutions of the past, provides a lens with which to view the present and future.